2020
DOI: 10.1002/jbm.a.36995
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembling hydrogel loaded with 5‐FU PLGA microspheres as a novel vitreous substitute for proliferative vitreoretinopathy

Abstract: The vitreous substitute for proliferative vitreoretinopathy (PVR) surgery remains an unmet clinical need in ophthalmology. In our study, we developed an in situ formed hydrogel by crosslinking polyvinyl alcohol (PVA) and chitosan as a potential vitreous substitute. 5-fluorouracil (5-FU) Poly (lactic-co-glycolic acid) (PLGA) microspheres were developed and loaded onto the PVA/chitosan hydrogels to treat PVR. In vitro, PVA/chitosan hydrogels at four concentrations were subjected to morphological, physical, rheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Hydrogel vitreous substitutes with direct injection mechanism 59,62,73,76,[81][82][83]94,110 (G' = 49.9 ± 31.3 Pa, n = 9 and G" = 26.3 ± 21.8 Pa, n = 9) have the closest modulus to the human vitreous, followed by thermogelling/in situ crosslinking hydrogels 37,96,100,101 (G' = 136 ± 33.1 Pa, n = 4 and G" = 28.9 ± 23.8 Pa, n = 4). The moduli of hydrogels with in situ crosslinking 34,69,93,97,98,104 (G' = 1626 ± 1031 Pa, n = 13 and G" = 338 ± 332 Pa, n = 6) or thermogelling 60,61,74,102 (G' = 2946 ± 2360 Pa, n = 4 and G" = 1206 ± 937 Pa, n = 4) mechanisms are, on average, more than two orders of magnitude higher than those of the natural human vitreous. Scatter plots of different hydrogel types ( Figure 4C) and injection mechanisms ( Figure 4D) highlight the widespread differences in both storage and loss modulus for current experimental hydrogel vitreous substitutes.…”
Section: The Strive For Improved Vitreous Substitutes and Intraocularmentioning
confidence: 98%
See 3 more Smart Citations
“…Hydrogel vitreous substitutes with direct injection mechanism 59,62,73,76,[81][82][83]94,110 (G' = 49.9 ± 31.3 Pa, n = 9 and G" = 26.3 ± 21.8 Pa, n = 9) have the closest modulus to the human vitreous, followed by thermogelling/in situ crosslinking hydrogels 37,96,100,101 (G' = 136 ± 33.1 Pa, n = 4 and G" = 28.9 ± 23.8 Pa, n = 4). The moduli of hydrogels with in situ crosslinking 34,69,93,97,98,104 (G' = 1626 ± 1031 Pa, n = 13 and G" = 338 ± 332 Pa, n = 6) or thermogelling 60,61,74,102 (G' = 2946 ± 2360 Pa, n = 4 and G" = 1206 ± 937 Pa, n = 4) mechanisms are, on average, more than two orders of magnitude higher than those of the natural human vitreous. Scatter plots of different hydrogel types ( Figure 4C) and injection mechanisms ( Figure 4D) highlight the widespread differences in both storage and loss modulus for current experimental hydrogel vitreous substitutes.…”
Section: The Strive For Improved Vitreous Substitutes and Intraocularmentioning
confidence: 98%
“…A big discrepancy in the number of publications on hydrogel vitreous substitutes and vitreous humor in the years 1995-2000 (9 publications and 0 publications, respectively) should be noted, considering the approval of silicone oil for use as a vitreous substitute by the Food and Drug Administration (FDA) in 1994. 58 Synthetic 33,34,59-91 and semisynthetic [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] hydrogels have been more common materials for experimental vitreous substitutes in recent years, while natural hydrogels 37,[109][110][111][112][113][114][115][116][117][118][119][120][121][122][123] were much more prevalent in the early years ( Figure 3B). The foldable capsular vitreous body (FCVB) is a different polymeric design for a vitreous substitute that is currently undergoing clinical trials in China.…”
Section: The Strive For Improved Vitreous Substitutes and Intraocularmentioning
confidence: 99%
See 2 more Smart Citations
“…Although detailed interactions between these stimulating factors remain incompletely understood, ocular fluid samples from eyes with PVR clearly demonstrate high expression of inflammatory cytokines (Kaneko et al., 2018 ). Studies using combined therapy (anti-proliferation and anti-inflammation) in experimental PVR also suggest the potential for better outcomes (Cardillo et al., 2004 ; Yu et al., 2020 ). We have previously demonstrated that loading DNR or DEX into pSiO2 microparticles can extend their vitreous half-lives from hours to days (Hou et al., 2015 ; 2016 ).…”
mentioning
confidence: 99%